(untitled) (LACCEI, 2024)
Due to the covid-19 pandemic, people were forced to spend the last 2 years in confinement due to the high rate of contagion that it presented. As a consequence, the term of telemedicine reappeared, many medical consultations went to the technological level, thus reducing the contact of people with the possible contagion from abroad, but the effectiveness of the consultations decreased since the touch and use of the equipment with those that doctors count to monitor the signals that the body provides to know its status. In this investigation, an embedded board with IoT functions was developed to monitor the vital signs of a person through analog and digital sensors, using a TCP protocol to transport the data. Using communication with the Ubidots web application for real-time data reading and data collection, thus creating a medical history to be analyzed by the doctor and having a better vision of possible risk scenarios in the patients health. The results were accepted as healthy people were examined in a controlled environment. The final prototype design proved to be effective and was reviewed by healthcare professionals who found that a tool like this could be very useful.